2020
DOI: 10.3390/nu12072153
|View full text |Cite
|
Sign up to set email alerts
|

Low-Glycemic-Index/Load Desserts Decrease Glycemic and Insulinemic Response in Patients with Type 2 Diabetes Mellitus

Abstract: Diabetes mellitus is a chronic disease whose prevalence is growing worldwide. Consumption of desserts with low glycemic index (GI) and low glycemic load (GL) in a balanced hypocaloric diet has a positive impact on anthropometric and metabolic parameters in patients with type 2 diabetes mellitus (T2DM). The aim of the present study was to evaluate the glycemic and insulinemic response after consumption of desserts with low GI/GL in patients with T2DM. Fifty-one patients consumed either 83 g of the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…They improve the taste of these beverages and have a very low glycemic index. They are also recommended by some authorities, albeit with some caution ( Argiana et al, 2020 ; Ashwell et al, 2020 ). Polyols are hydrogenated carbohydrates used as sugar substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…They improve the taste of these beverages and have a very low glycemic index. They are also recommended by some authorities, albeit with some caution ( Argiana et al, 2020 ; Ashwell et al, 2020 ). Polyols are hydrogenated carbohydrates used as sugar substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence could play a vital role in lowering diabetic complications by 20%. Recently, a study evaluated the glycemic response of type-2 diabetes patients after feeding a low-GI dessert to them, and it was observed that the area under the curve was significantly lower as compared to that of control [85]. A review compiled the results reported by the studiesinvolving the consumption of low-GI food products and analyzing its effect on postprandial hyperglycemia.…”
Section: Diabetesmentioning
confidence: 99%
“…Alfalfa as a dietary fiber source plays a physiological role in improving diabetes, lowering blood pressure, lowering blood lipid, and preventing cardiovascular diseases (Anderson et al., 2009 ; Nuttall, 1993 ). In daily life, dietary fiber is applied to bread, drinks, desserts, and other foods (Argiana et al., 2020 ; Ibrügger et al., 2012 ; Kurek, 2015 ). In addition, alfalfa saponins can also reduce the amount of blood lipid, regulate the level of cholesterol, eliminate free radicals, regulate immunity, and prevent cardiovascular diseases (Dong et al., 2007 ; Malinow et al., 1977 , 1979 ).…”
Section: Introductionmentioning
confidence: 99%